Implementasi Model Pembelajaran Jigsaw Dalam Upaya Meningkatkan Kemampuan Berpikir Kritis Dan Hasil Belajar Biologi Siswa Kelas XI - Tuharlan Efendi (University of Bengkulu, 2020)
The aims of this study were to determine the improvement of critical thinking skills and biology learning outcomes of XI grade students of SMA Negeri 5 Rejang Lebong through the implementation of the Jigsaw learning model. Jigsaw learning model is a learning model that not only provides opportunities for students to develop cognitive abilities, but also develops social activities. This type of research conducted in this study is Classroom Action Research (CAR) or Classroom Action Research (CAR) with 2 Cycles. The subjects of this class action research were 19th grade students of Natural Sciences 2 with a total of 19 students. This subject selection is because based on the average grade of class, class XI IPA 2 has the lowest average value. The test instrument used consisted of tests of critical thinking skills and learning achievement tests. The results showed the average value of students' critical thinking skills in the first cycle was 67.78. In cycle II the average value of students' critical thinking skills was 84,706. The average value of student learning outcomes in the first cycle is 66.4 with classical learning completeness is 30%. In the second cycle was 82.7 with a classical learning completeness of 79.31%. Based on student value data it is concluded that the implementation of the Jigsaw learning model can improve critical thinking skills and biology learning outcomes of students of class XI IPA 2 at SMA Negeri 5 Rejang Lebong.